Pengaruh Kualitas Jasa Terhadap Tingkat Kepuasan Mahasiswa Akuntansi dalam Mengikuti Pendidikan Profesi Akuntansi (PPAk) - Suwaldiman -; Afuan Fajrian Putra (Jurnal Aplikasi Bisnis, 2016)
This research examines whether there are any differences among the service quality against the satisfaction of PPAk students; and tests the impacts of service quality to the students' satisfaction. Service quality is represented by reliability, responsiveness, assurance, empathy, and tangible. This research is conducted to the students who are undertaking accounting profession education in UII, UGM, STIE YKPN and Sanata Darma of University.Purposive sampling is employed in which 100 samples were distributed and 87 of those are processed. Based on the paired samples T Test and multiple linear regression analysis, this research reveals that there are no differences found among the service quality against the satisfaction of PPAk students. In addition, reliability, responsiveness, empathy^ and tangible affect positively to the students' satisfaction. However, assurance does not affect positively to the students *satisfaction.